Race, Disability and COVID-19: A DisCrit Analysis of Theological Education - Fears, Barbara A. (Religions, 2021)
The coronavirus pandemic of 2020 has generated public debate and private discussion about systemic racism in contemporary U.S. society and the ill preparedness and misdirected focus of clergy responding to this crisis. Later research will reveal reasons trained clergy called denominational offices, requesting assistance to address the needs of patients and parishioners, and initiated lawsuits demanding to gather for worship against medical advice and government mandates. While theological educators cannot anticipate every emergency awaiting graduates, U.S. history records national crises (i.e., hurricanes, mass shootings, BLM protests, etc.) that repeat. Practical theology course offerings, course content and course assignments, therefore, should be designed to prepare students to lead in anticipation of personal and communal tragedies. As professors introduce students to theory/theorists, we must also create space for the development of critical consciousness about and praxis for: problem solving, advocacy, race relations, relationship building, crisis management, identity politics, privilege, implicit curriculums and race-based disparities in health care, policing, religion, education, etc. Critical Race Theorists assert that this nation’s colonial past still plagues contemporary behaviors, employing the framework of Disability Studies and CRT (Dis/Crit), I analyze theological education to address what has been identified as racial paterfamilias in the institution, which may explain our colonial/capitalist response to COVID-19.